The case of Hermie the missing hamster - Preller, James; Copyright Paperback Collection (Library of Congress) (New York : Scholastic Inc, 1998)
The clever, puzzle-crazy Jigsaw Jones utilizes his top-secret detective journal and enlists the help of his ace partner, Mila, to track down a missing hamster.
"A LIttle Apple paperback."
G2
Keywords: Mystery and detective stories; Detective and mystery stories -- Juvenile fiction